2019
DOI: 10.1101/808808
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A functional corona around extracellular vesicles enhances angiogenesis during skin regeneration and signals in immune cells

Abstract: words)Allogeneic regenerative cell therapy has shown surprising results despite lack of engraftment of the transplanted cells. Their efficacy was so far considered to be mostly due to secreted trophic factors. We hypothesized that extracellular vesicles (EVs) can also contribute to their mode of action. Here we provide evidence that EVs derived from therapeutic placental-expanded (PLX) stromal cells are potent inducers of angiogenesis and modulate immune cell proliferation in a dose-dependent manner.Crude EVs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 72 publications
(97 reference statements)
2
21
0
Order By: Relevance
“…Purified hiPSC-ECs formed pronounced vascular networks in the presence but not absence of hPL. To gain further insight into the mechanism of hPL-based angiogenesis support 26 , 30 we purified extracellular vesicles (EVs) from hPL, because we observed in another study that EVs can mediate such trophic effects 48 . The hPL-derived presumably platelet lipoprotein-enriched EVs 48 supported angiogenesis of hiPSC-ECs significantly in a dose-dependent manner even in the absence of otherwise essential externally added vascular endothelial growth factor (VEGF).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Purified hiPSC-ECs formed pronounced vascular networks in the presence but not absence of hPL. To gain further insight into the mechanism of hPL-based angiogenesis support 26 , 30 we purified extracellular vesicles (EVs) from hPL, because we observed in another study that EVs can mediate such trophic effects 48 . The hPL-derived presumably platelet lipoprotein-enriched EVs 48 supported angiogenesis of hiPSC-ECs significantly in a dose-dependent manner even in the absence of otherwise essential externally added vascular endothelial growth factor (VEGF).…”
Section: Resultsmentioning
confidence: 99%
“…The clonogenic potential of fibroblasts, endothelial cells and hiPSC-derived cells was assessed according to published protocols 44 , 47 . The purification of extracellular vesicles from hPL supporting the angiogenic potential of ECs and hiPSC-ECs as well as the network formation assay was previously established and performed according to a published protocol 48 .…”
Section: Methodsmentioning
confidence: 99%
“…Particle-rich media, due to supplementation with human platelet lysate or fetal bovine serum, were instantly used to acquire bone marrow stromal cell-derived EVs for cell-free treatment of graft-versus-host disease [ 31 ]. Alternatively, pre-existing particles could be depleted before initiation of cell culture [ 32 ]. Chemically defined serum-free medium offers the advantage of a lower initial particle count, thus enabling a more precise quantification of EVs secreted by donor cells into the conditioned medium over time.…”
Section: Discussionmentioning
confidence: 99%
“…Purified hiPSC-ECs formed pronounced vascular networks in the presence but not absence of hPL. To gain further insight into the mechanism of hPL-based angiogenesis support 11,13 we purified extracellular vesicles (EVs) from hPL, because recent evidence indicated that EVs can mediate such trophic effects 41 . The hPL-derived EVs supported angiogenesis of hiPSC-ECs significantly in a dose-dependent manner even in the absence of otherwise essential externally added vascular endothelial growth factor (VEGF).…”
Section: Platelet-derived Factors Promote Mesodermal Specification Ofmentioning
confidence: 99%
“…The clonogenic potential of fibroblasts, endothelial cells and hiPSC-derived cells was assessed according to published protocols 50,51 . The purification of extracellular vesicles from hPL supporting the angiogenic potential of ECs and hiPSC-ECs as well as the network formation assay was previously established and performed according to a published protocol 41 .…”
Section: Clonogenicity Ev Concentration and Network Formation Assaymentioning
confidence: 99%